Lesions in the Fundus of the Eye in Patients with Acute Leukemia. Who Has, When and Why? - T. A. Mitina; P. I. Semenikhina; E. E. Grishina; Z. M. Kharasova (Oftalʹmologiâ, 2024)
Acute leukemia is a formidable disease that often leads to the death of the patient from the underlying disease or the consequences of severe chemotherapy treatment. Many prognostically unfavorable factors are known, including genetic and epigenetic ones. The review is devoted to the prognostic significance of changes in the fundus in patients with acute leukemia. According to various literature sources, ophthalmic manifestations of leukemia can be observed in 9-90% of cases. The data is obtained from the sources: eLibrary.RU, in the international PubMed database, as well as on the electronic websites of specialized scientific journals. Retinal hemorrhages, according to various authors, are associated with changes in peripheral blood. At the moment, there is no consensus on whether eye damage in acute leukemia is a bad prognostic sign. Are changes in peripheral blood related to pathologies on the fundus? It is not clear in which case, and in which patients, they may indicate an unfavorable prognosis. Is there a relationship between fundus lesions in acute leukemia and already known genetic and epigenetic adverse prognostic factors? All these unresolved issues require further detailed research of patients with acute leukemia and changes in the fundus.